SAT0137 PATIENTS (PTS) SWITCHED TO SARILUMAB FROM ADALIMUMAB ACHIEVE CLINICALLY IMPORTANT IMPROVEMENTS IN RA DISEASE ACTIVITY: RESULTS FROM MONARCH TRIAL OPEN-LABEL EXTENSION (OLE). (June 2019) - Burmester, Gerd Rüdiger; Amital, Howard; Rubbert-Roth, Andrea; Hoogstraten, Hubert van; Gervitz, Leon M.; Thangavelu, Karthinathan; John, Gregory St; Genovese, Mark C.
Abstract : Background: In MONARCH (NCT02332590 ), sarilumab monotherapy (200 mg subcutaneously [SC] every 2 weeks [q2w]) demonstrated superiority to adalimumab monotherapy (40 mg SC q2w) in DAS28-ESR, ACR20/50/70 response, HAQ-DI, and CDAI in pts with RA and inadequate response/intolerance to methotrexate. Objectives: To assess long-term safety/efficacy in RA pts continuing sarilumab or switching from adalimumab to sarilumab monotherapy in the ongoing OLE of MONARCH. Methods: Pts completing MONARCH were eligible for the OLE, in which they received sarilumab 200 mg SC q2w. Efficacy and safety data were reported up to OLE Wk 48 and March 2017, respectively. Responder rates were based on the intent-to-treat population. Continuous efficacy endpoints were based on the observed population. Results: Of 369 pts enrolled in MONARCH, 320 (87%) entered OLE (switch: n=155; continuation: n=165). By safety data cut-off, pt attrition was similar in switch (24; 15.5%) and continuation groups (22; 13.3%), as were treatment-emergent adverse events (AEs) (switch: 76.1%, 267.4/100 PY; continuation: 70.9%, 230.2/100 PY) and infections (switch: 41.9%; continuation: 35.8%). For DAS28-ESR and CDAI endpoints, >40% of switch pts achieved a minimally important difference (MID) improvement from OLE baseline by OLE Wk 12, increasing to >50% by OLE Wk 48. Additionally, >40% of switch pts achieved a MID in DAS28-CRP and a minimally clinically important difference (MCID) in HAQ-DI from OLE baseline to OLE Wk 48 (Fig). Of pts achieving CDAI ≤10 from baseline OLE to Wk 24 of the OLE, 70.7% (switch group) and 83.5% (continuation group) achieved sustained response at OLE Wks 36 and 48. In the randomized controlled phase, response rates were higher in sarilumab-treated than adalimumab-treated pts, hence fewer pts in the continuation group achieved additional MID during OLE (data not shown). AEs of special interest are reported (Table). Two deaths occurred in the switch group (malignancy; cerebrovascular accident) versus one in the continuation group (subarachnoid hemorrhage). No GI-related AEs (ulcerations/perforations/diverticulitis) were observed. Conclusion: Pts switched from adalimumab to sarilumab experienced clinically meaningful improvements in signs and symptoms of RA. Safety observations in OLE were generally consistent with those in MONARCH. Acknowledgement: Study funding and editorial support (Helen Johns, Adelphi) were provided by Sanofi Genzyme and Regeneron Pharmaceuticals, Inc. These data have been submitted to the 2019 APLAR-ARA and SER meetings. Disclosure of Interests: Gerd Rdiger Burmester Consultant for: Roche, Sanofi-Genzyme, Speakers bureau: Roche, Sanofi-Genzyme, Howard Amital Grant/research support from: Pfizer, AbbVie, Janssen, Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Merck Sharp & Dohme, Consultant for: Pfizer, Merck Sharp & Dohme, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Hubert van Hoogstraten Shareholder of: Sanofi, Regeneron, Novartis, Grant/research support from: Zambon, Employee of: Sanofi, Leon M. Gervitz Shareholder of: Sanofi, Union Chimique Belge, Abbvie, Celgene, Amgen, Employee of: Sanofi, Karthinathan Thangavelu Shareholder of: Sanofi, Employee of: Sanofi, Gregory St John Shareholder of: Regeneron Pharmaceuticals Inc, Employee of: Regeneron Pharmaceuticals Inc, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm